UJI PATOGENESITAS BEBERAPA ISOLAT BAKTERI SIMBION NEMATODA ENTOMOPATOGEN TERHADAP LARVA KROP KUBIS Crocidolomia pavonana - Aris Cahyono; Arika Purnawati; Tri Mudjoko; Presti Mardiyani (Plumula : Berkala Ilmiah Agroteknologi, 2019)
To control pest Crocidolomia pavonana in cabbage plants are still based on chemical and mechanical control. The methode is considered ineffective because excessive use of chemicals has a negative effect on the comodity and the environment. The application of plant protection technology using Biological Control Agents (BCA) is one of the solutions given. One of them is entomopathogenic nematode (EPN). The advantage possessed by EPN is the symbiosis with the symbiont bacteria that secretes toxins so that it can immobilize the host quickly. Based on this, a study was conducted to determine the pathogenicity of symbionic bacteria against Crocidolomia pavonana larvae, so that they could be developed as bioentomopathogenic in the Integrated Pest Control concept. The pathogenicity test on Crocidolomia pavonana larvae was carried out using 4 treatments placed in a Completely Randomized Design (CRD) with each treatment repeated 6 times. The results showed that in the three days of observation, the four bacterial isolates had the same ability to kill Crocidolomia pavonana larvae with the highest percentage of 100% and the lowest 88.9%. Thus the four isolates can be used as an alternative in controlling Crocidolomia pavonana larvae.